2015
DOI: 10.1007/s10854-015-2800-2
|View full text |Cite
|
Sign up to set email alerts
|

Humidity sensing properties of CeO2–NiO nanocomposite materials

Abstract: CeO 2 -NiO composites were prepared by a simple grind method followed by a heat-treatment process and characterized by X-ray diffraction, transmission electron microscope and nitrogen adsorption-desorption test. Humidity sensing properties of CeO 2 -NiO composites with different mass ratios were studied. The optimal result was obtained for the sample with CeO 2 -NiO mass ratio of 0.5. The impedance of the sensor changes more than five orders of magnitude within the humidity range from 11 to 95 % relative humid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…For example, Singla et al 27 reported changes in linear response at 40-60% RH for a polyaniline/Mn 3 O 4 composite doped with organic/inorganic acid. Similarly, Biswas et al 21 reported changes at 55-77% RH for ZnO nanotip arrays, Li et al 26 reported changes at 33-54% RH for a Ce 2 O-NiO composite, and Chung et al 50 reported changes at 45% RH for anodic aluminum oxide. Aer the abrupt change, the response continued to increase in the same direction, up to the present results at 50-60% RH.…”
Section: Cu/cu 2 O Colloidal Solutionmentioning
confidence: 96%
See 3 more Smart Citations
“…For example, Singla et al 27 reported changes in linear response at 40-60% RH for a polyaniline/Mn 3 O 4 composite doped with organic/inorganic acid. Similarly, Biswas et al 21 reported changes at 55-77% RH for ZnO nanotip arrays, Li et al 26 reported changes at 33-54% RH for a Ce 2 O-NiO composite, and Chung et al 50 reported changes at 45% RH for anodic aluminum oxide. Aer the abrupt change, the response continued to increase in the same direction, up to the present results at 50-60% RH.…”
Section: Cu/cu 2 O Colloidal Solutionmentioning
confidence: 96%
“…This abrupt change in linear response with increasing RH has been reported for various materials. 21,26,27,50 The RH range within which the response changes varies from material to material, and surface properties such as surface roughness and porosity promote proton hopping. For example, Singla et al 27 reported changes in linear response at 40-60% RH for a polyaniline/Mn 3 O 4 composite doped with organic/inorganic acid.…”
Section: Cu/cu 2 O Colloidal Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, more and more researchers are paying their attention to exploitation of materials for humidity sensor with excellent humidity sensing properties including high sensitivity, linear response, and fast response speed [6][7][8][9]. One-dimensional (1D) nanostructures, such as nanofibers, nanowires, and nanotubes, have been gained considerable attention in humidity sensing because of their special physical and chemical properties [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%